Development of a new pultrusion equipment to manufacture thermoplastic matrix composite profiles - Novo, P. J. (2014)
ECCM15 - 15TH EUROPEAN CONFERENCE ON COMPOSITE MATERIALS, Venice, Italy, 24-28 June 2012